2012
DOI: 10.1177/0194599812450855
|View full text |Cite
|
Sign up to set email alerts
|

Biocompatibility Comparison of Novel Soft Tissue Implants vs Commonly Used Biomaterials in a Pig Model

Abstract: Subjective scoring of pathology slides and measurement of capsule thickness appeared to show differences between the materials, but these differences require a larger number of subjects and proper statistical analysis to assess. The robust foreign body reaction elicited by the polypropylene/silicone-based scaffold argues against the use of this material in future studies. The authors advocate using inert biodegradable substances for future bioscaffold constructs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
15
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 34 publications
2
15
0
Order By: Relevance
“…In the late period (i.e., after 90 days) quite a broad band of fibrous connective tissue was present. In a study involving a pig model, Kolb et al also showed a continuing weakly intensified inflammatory reaction after implanting polypropylene thread, which minimized over in time, and fibrous connective tissue appeared around the thread [20]. In the present study, the presence of a thin band of loose connective tissue was observed around resorbable glyconate threads in muscle tissue in the early period (i.e., up to the 14 th day).…”
supporting
confidence: 68%
“…In the late period (i.e., after 90 days) quite a broad band of fibrous connective tissue was present. In a study involving a pig model, Kolb et al also showed a continuing weakly intensified inflammatory reaction after implanting polypropylene thread, which minimized over in time, and fibrous connective tissue appeared around the thread [20]. In the present study, the presence of a thin band of loose connective tissue was observed around resorbable glyconate threads in muscle tissue in the early period (i.e., up to the 14 th day).…”
supporting
confidence: 68%
“…Synthetic polymers can be tailored to achieve desirable degradation profiles or rates of growth factor delivery, but it has long been known that additional modifications are necessary to promote improved cell attachment 13,14 . While such approaches are being used to better understand and direct cell behavior 1517 , degradation products of some synthetic materials have been associated with inflammatory and foreign body responses in certain conditions 1820 . Some naturally-based materials such as the polysaccharide alginate can persist for long periods of time in vivo , but like synthetic polymers require modification in order to have tunable rates of degradation or present cell-binding motifs that cells would encounter in the three-dimensional environment 21,22 .…”
Section: Introductionmentioning
confidence: 99%
“…In total eight studies assessed the host response to allografts in both animals and humans. The time since implantation ranged from 2 days up to 65 weeks [ 20 , 26 , 27 , 36 40 ].…”
Section: Resultsmentioning
confidence: 99%
“…Human cadaveric dermis and cadaveric fascia have been found to be well integrated onto the abdominal wall [ 37 , 40 , 41 ] and rectus muscle [ 36 , 38 ] in different animals, including rats, rabbits, and pigs, as noted by moderate fibroblast infiltration, new collagen production, and neovascularization where materials were implanted from 2 days up to 62 weeks. Human cadaveric dermis, after 12 weeks of implantation, was similarly well integrated into vaginal tissues of rabbits.…”
Section: Resultsmentioning
confidence: 99%